2023
DOI: 10.1080/20008066.2023.2263314
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and clinical consequences of post-traumatic and dissociative symptoms in people with depressive symptoms: a one-year follow-up study

Hong Wang Fung,
Anson Kai Chun Chau,
Suet Lin Hung
et al.

Abstract: Background: Recent studies found that post-traumatic and dissociative symptoms are common in people with depressive symptoms. Although a trauma-related subtype of depression has been proposed, little is known about the persistence and clinical consequences of these symptoms. Objective: This one-year follow-up study investigated the persistence and clinical consequences of post-traumatic and dissociative symptoms in people with depressive symptoms. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…In this 9-month study, we found that 63.6% of participants with baseline dissociative symptoms continued to exhibit dissociative symptoms at follow-up. This figure is similar to those reported in another recent study with a sample of English-speaking adults with self-reported depressive symptoms ( N = 152) – in that study, 58.4% of participants with clinically significant dissociation (Multiscale Dissociation Inventory [MDI] ≥ 67) at baseline remained to score 67 or above on the MDI after one year (Fung, Chau, et al, 2023 ). The persistence rates (58.4% to 63.6%) in these two clinically and socioculturally different samples, while consistent, are much higher than those reported in the Finnish sample (28.6%) (Maaranen, 2008 ).…”
Section: Discussionsupporting
confidence: 89%
“…In this 9-month study, we found that 63.6% of participants with baseline dissociative symptoms continued to exhibit dissociative symptoms at follow-up. This figure is similar to those reported in another recent study with a sample of English-speaking adults with self-reported depressive symptoms ( N = 152) – in that study, 58.4% of participants with clinically significant dissociation (Multiscale Dissociation Inventory [MDI] ≥ 67) at baseline remained to score 67 or above on the MDI after one year (Fung, Chau, et al, 2023 ). The persistence rates (58.4% to 63.6%) in these two clinically and socioculturally different samples, while consistent, are much higher than those reported in the Finnish sample (28.6%) (Maaranen, 2008 ).…”
Section: Discussionsupporting
confidence: 89%
“…Participants with a clinical diagnosis of a reading disorder, dementia or intellectual disabilities were excluded. The methodology, including part of the baseline data, has been published elsewhere (Fung et al, 2023).…”
Section: Methodsmentioning
confidence: 99%